Potential of Sappan Wood, Purple Cabbage and Beetroot Extract in Sperm Staining - Mamay, Mamay; Ernawati, Ernawati; Nurisani, Astari (Universitas Nahdlatul Ulama Surabaya, 2023)
Examination of sperm morphology is an essential criterion for evaluating male fertility. This examination can be done by staining sperm cells with various techniques to facilitate the visualization of sperm cells. Several other methods that can be used to evaluate sperm morphology are Eosin-nigrosin, AgNO3 staining, Papanicolaou, Diff Quick and Giemsa. However, using these synthetic dyes can harm the environment and water sources because they prefer to decompose. The natural dye derived from environmentally friendly plants expected to minimize hazardous waste. This study aimed to identify and compare the potency of several natural dyes derived from purple cabbage, sappan wood and beetroot, which have not been studied in sperm studies. Sperm obtained from 30 men in the campus area and underwent 3-5 days of abstinence from intercourse in preparation for sampling. The sperm stained with natural dye, and their quality compared with WHO standard Papanicolaou. Extracts of sappan wood, purple cabbage and beetroot are made with various mordant alum, ethanol and acetic acid compositions. The study's results showed that the presence of mordant increased the staining quality of sperm with sappan wood and purple cabbage extracts. The use of acid improves the quality of sperm staining with beet extract. There was no different between dyeing with beetroot extract in various solvent compositions and dyeing with Papanicolaou to color all sperm components (p> 0.05). The results showed that beetroot extract has a high potential to evaluate sperm morphology.